The Dual Regulation Effects of ESR1/NEDD4L on SLC7A11 in Breast Cancer Under Ionizing Radiation - Liu, Rui; Liu, Lin; Bian, Yan; Zhang, Shinan; Wang, Yue; Chen, Huajian; Jiang, Xinyue; Li, Guanghui; Chen, Qing; Xue, Chang; Li, Mengke; Liu, Lianchang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Radiotherapy is one of the most important treatments for breast cancer. Ferroptosis is a recently recognized form of regulated cell death that is characterized by lipid peroxidation. However, whether ionizing radiation (IR) could induce ferroptosis in breast cancer and how it works remain unknown. Bioinformatics analysis were performed to screen ferroptosis-related genes differentially expressed in breast tumor tissue and normal tissue. Then, breast cancer cell lines with different estrogen receptor (ER) phenotypes were used for studies in vitro, including ER-positive (MCF-7 and ZR-75-1) and ER-negative (MDA-MB-231) cells. The dynamic changes of mRNA and protein levels were examined after x-ray of 8 Gy by qRT-PCR and Western blotting, respectively. Immunoprecipitation (IP) was used to explore the interaction between proteins. Luciferase assay was used to analyze the transcriptional regulation effect of ESR1 on SLC7A11. BODIPY C11 and trypan blue dyes were used to determine lipid peroxidation and cell death, respectively. The result showed that the ferroptosis-related gene SLC7A11 was higher in breast cancer tissues compared with normal tissues and associated with poor survival. A positive correlation exists between ESR1 and SLC7A11 expression. ESR1 promoted SLC7A11 expression at the early stage after IR. ESR1/SLC7A11 knockdown significantly enhanced IR-induced ferroptosis in ER-positive cells. At 12 h after IR, the IP data showed the interaction between E3 ubiquitin ligase NEDD4L and SLC7A11 increased, followed by the ubiquitylation and degradation of SLC7A11. Thus, SLC7A11 expression was regulated by both ESR1 and NEDD4L, in opposite ways. For the first time, we elucidated that ESR1 and NEDD4L functioned together after radiation treatment and finally induced ferroptosis in breast cancer cells, which provides novel insight into the guidance of clinical treatment of breast cancer.